2018
DOI: 10.20944/preprints201811.0064.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Significant Role of Different Magnesium: Carbonate Minerals Induced by Moderate Halophile <em>Staphylococcus epidermis</em> Y2

Abstract: Carbonate precipitation induced by microorganism has become a hot spot in the field of carbonate sedimentology, while the effect of different magnesium on biominerals has rarely been studied. Therefore, magnesium sulfate and magnesium chloride were used to investigate the significant role played on carbonate minerals. In this study, Staphylococcus epidermidis Y2 was isolated and identified by 16S rDNA homology comparison. The ammonia, pH, carbonic anhydrase, carbonate and bicarbonate ions were investigated. Th… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 121 publications
(159 reference statements)
2
0
0
Order By: Relevance
“…As observed from EDX profiles, strong signal peaks with considerable percentage of carbon, oxygen and calcium were detected at 0.277, 0.525 and 3.69 keV, respectively. Notably, Na and Cl peaks were also detected as small signals, suggesting them to be residuals from media ingredients incorporated in precipitated crystals during the ureolysis process as reported by Han et al 34 In addition, P and S peaks were observed at 2.013 and 2.3 keV, respectively, implying the biological origin of CaCO 3 crystals, both elements being building blocks of vital biomolecules such as proteins, nucleic acids, phospholipids and polysaccharides. 35,36 As suggested by Ghosh et al, 37 such elements could donate stabilization for biosynthesized precipitates.…”
Section: Crystal Identification and Characterizationsupporting
confidence: 61%
“…As observed from EDX profiles, strong signal peaks with considerable percentage of carbon, oxygen and calcium were detected at 0.277, 0.525 and 3.69 keV, respectively. Notably, Na and Cl peaks were also detected as small signals, suggesting them to be residuals from media ingredients incorporated in precipitated crystals during the ureolysis process as reported by Han et al 34 In addition, P and S peaks were observed at 2.013 and 2.3 keV, respectively, implying the biological origin of CaCO 3 crystals, both elements being building blocks of vital biomolecules such as proteins, nucleic acids, phospholipids and polysaccharides. 35,36 As suggested by Ghosh et al, 37 such elements could donate stabilization for biosynthesized precipitates.…”
Section: Crystal Identification and Characterizationsupporting
confidence: 61%
“…Notably, Na and Cl peaks were also detected in a small percentage, suggesting to be residuals from media ingredients that incorporated in precipitated crystals during ureolysis process as reported by Han et al, (2018). In addition, P and S peaks were observed at emission peaks 2.013 and 2.3 keV, correspondingly, implying the biological origin of CaCO3 crystals.…”
Section: Crystals Identification and Characterizationsupporting
confidence: 58%